2003
DOI: 10.1046/j.1365-2567.2003.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional Toll‐like receptor‐4 mutations on the immune response to human and experimental sepsis

Abstract: SUMMARYGenetically determined responsiveness to microbial stimuli such as lipopolysaccharide (LPS) may affect the pathophysiology of human sepsis. The D299G mutation in human Toll-like receptor-4 (TLR4) impairs LPS signalling in homozygous and heterozygous individuals. To investigate whether the presence of the TLR4(D299G) mutation may correlate with the development or outcome of sepsis following major visceral surgery the presence of TLR4(D299G) mutation was analysed in 307 Caucasian patients (154 without and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 20 publications
4
65
0
3
Order By: Relevance
“…Our genetic findings in heterozygous individuals support a model in which alleles 896G and 1196T act in a dominant fashion with respect to the wild-type alleles in their association with resistance to LD. Similarly, previous genetic studies (19)(20)(21)(22)(23)(32)(33)(34)(35) with these TLR4 SNPs suggest that altered susceptibility to infection is found in heterozygous individuals.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Our genetic findings in heterozygous individuals support a model in which alleles 896G and 1196T act in a dominant fashion with respect to the wild-type alleles in their association with resistance to LD. Similarly, previous genetic studies (19)(20)(21)(22)(23)(32)(33)(34)(35) with these TLR4 SNPs suggest that altered susceptibility to infection is found in heterozygous individuals.…”
Section: Resultssupporting
confidence: 56%
“…Previous association studies (19)(20)(21)(22)(23)(32)(33)(34)(35) with SNPs A896G and C1196T have shown either no effect or an association with increased risk from infection. The conditions that showed an association with increased infectious risk include mortality from systemic inflammatory response syndrome, severe acute infections (e.g., pneumonia, pyelonephritis, peritonitis, diverticulitis, and sepsis), septic shock, Gram-negative bacteremia, and respiratory syncytial virus bronchiolitis (19)(20)(21)(22)(23).…”
Section: Resultsmentioning
confidence: 90%
“…Because TLR4 primarily recognizes LPS of Gram-negative bacteria (12) and expression levels correlate with LPS susceptibility in mice (36), the entire expression pattern in neonatal sepsis might reflect the fact that Gram-positive microorganisms are responsible for the majority of cases. In experimental endotoxemia and adults with Gram-positive as well as Gram-negative sepsis, TLR4 expression on monocytes did not change and decreased on granulocytes in experimental endotoxemia (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is tempting to postulate that increased expression of TLRs would have a beneficial effect in trauma patients. Polymorphism of TLRs was one of the factors that increased the susceptibility to infections caused by particular bacteria, but in patients with mixed severe infections did not show any significant effect on their course and outcome [39]. In some experimental studies a lack of TLRs increased the susceptibility to infections in mice [40] and caused disorders in inflammatory mediator secretion as well as disorders in phagocytosis and antigen presentation [41][42][43].…”
Section: Tlr-dependent Anti-bacterial Responsementioning
confidence: 99%